Status of personality who lives in Marutha nilam according to the Yaakajin ilakanam in Siddha Medicine - Sathiyaseelan, V.; Tharshini, R. (Unit of Siddha Medicine, University of Jaffna, 2018)
Vazhi, Azhal and Aiyam are the three humors which are the life constituents of the human body. According to the Siddha fundamental geographical distribution of the land closely inter related withhuman wellbeing of the health. The three humors (Vazhi, Azhal,Aiyam) combine among them in ten different combinations. Basically they occur because of the variations of the three humors. Yaakajinilakanamdepends on geographical variations.Out of five geographical land (Neithal, Pala, Marutham, Mullai, Kurinchi)Maruthamis the agriculture land, which will drive out the disease of all the three humors. (Uthamarajan, Siddha MaruthuvangaSurukkam). The permission was taken from the authority.Data were collected with the help of interviewer administered questionnaire for period of June to November 2017, 100 healthy people randomly selected for the above study. Based on the result reviled, 45% of males and 55% of females were identified. According to the age, 28% of peoples are significant of (61-70). Among these population 37% sedentary workers, 33% farmers and 30% of people are House wife. Among these population according to the Yaakajinilakanam, 2% vazhi, 3% Aiyam, 3% Aiyaazhal, 3% Vazhi aiyam, 4% Aiyavazhi, 5% Azhal, 9% Vazhiazhal, 17% Azhalvazhi, 18%Azhal aiyam, 36% Sannipatham. Most of the people are Sannipatham in the marutham. Among the five geographical landmarutham is the best land for the lead a healthy life without disease and drive out the disease of all the three humors. Based on the results also significant percentage of the people consist of Sannipatham. Out of ten Yaakajinilakanam, Sannipatham is a healthy personality according to the Siddha fundamental. When we know about the individual of Yaakajin ilakanam, we can easily diagnose the disease and treat the patient successfully.
Keywords: Marutha nilam; Yaakajin ilakanam; Personality